2017
DOI: 10.1371/journal.pone.0175790
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteins mediate depression’s association with dementia

Abstract: The latent variable “δ” (for “dementia”) uniquely explains dementia severity. Depressive symptoms are independent predictors of δ. We explored 115 serum proteins as potential causal mediators of the effect of depressive symptoms on δ in a large, ethnically diverse, longitudinal cohort. All models were adjusted for age, apolipoprotein E, education, ethnicity, gender, hemoglobin A1c, and homocysteine, and replicated in randomly selected 50% subsets. Alpha1-antitrypsin (A1AT), FAS, Heparin-binding EGF-like Growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 59 publications
(66 reference statements)
1
21
0
Order By: Relevance
“…INFLAMMATION accounts for 5%–10% of dT2A's variance, which we have previously shown to be strongly associated with CDR‐SB and the diagnosis of clinical “AD” [16]. Its effect on δ is independent of other recognized dementia risks (e.g., age, APOE, and depression) which are mediated by yet other serum proteins [11–13]. In their aggregate, INFLAMMATION and those dementia risks account for between 24% (ADNI) to 38% (TARCC) of dT2A's variance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…INFLAMMATION accounts for 5%–10% of dT2A's variance, which we have previously shown to be strongly associated with CDR‐SB and the diagnosis of clinical “AD” [16]. Its effect on δ is independent of other recognized dementia risks (e.g., age, APOE, and depression) which are mediated by yet other serum proteins [11–13]. In their aggregate, INFLAMMATION and those dementia risks account for between 24% (ADNI) to 38% (TARCC) of dT2A's variance.…”
Section: Discussionmentioning
confidence: 99%
“…Unmodeled influences on the observed protein concentrations could explain nondementing effects of the same biomarker in other organs or even in brain, given that not all cognitive domains are functionally salient [3,45]. Several δ‐related serum protein biomarkers mediate both age and depression's independent and mutually adjusted effects on δ (apparently as contributors to independent competing processes) [11,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All six selected proteins have been previously reported to associate with dementia phenotype “δ” in ethnicity-adjusted models from TARCC cohort 41,42 . Details about concept and utility of δ is can be obtained from past publications 4345 46 .…”
Section: Mainmentioning
confidence: 99%
“…Contemporary data emphasize the role of processes of neuroplasticity and neuroinflammation in pathogenesis of endogenous mental disorders, including schizophrenia [30][31][32][33]. In particular, it has been shown that high activity of leukocyte elastase (LE) and alpha-1 proteinase inhibitor (α − 1 − PI) has been associated with exacerbation of endogenous mental disorders, while in remission their activity decreased [33,34]. Moreover, these immunological parameters not only reflected the acuity of illness, but also may precede the clinical signs of relapse [33].…”
Section: Introductionmentioning
confidence: 99%